Filters and Ideals in a Fuzzy Lattice - Daoula, Chaima (Faculty of Mathematics and Computer Sciences Department of Mathematics - Option: Algebra and Discrete Mathematics, 2021)
In this memory, we have studied some de nitions and properties of the fuzzy lattice and we have seen some types of fuzzy lters and fuzzy ideals in a fuzzy lattice. we noticed that the fuzzy lattice isomorphism preserves the nature and type of fuzzy lters ( fuzzy ideals).
Keywords: Fuzzy sets, fuzzy lters, fuzzy ideals, fuzzy lattice isomorphism.